Distressed Financial Institutions in Thailand : Structural Weaknesses. Support Operations and Economic Consequences. (IMF Working Papers; Working Paper, 1989)
The Thai financial system faced a crisis in 1983. Weak managerial practices and an inadequate legal and regulatory framework were associated with a gradual deterioration in many financial institutions' balance sheets; these weaknesses were brought to the fore by a sharp economic downturn in the first half of the 1980s. The Thai authorities took a number of measures to maintain stability in the financial system and to restructure insolvent financial institutions, including a substantial strengthening in the legal and regulatory framework. The crisis has impacted on the government budget deficit and caused shifts in the demand for financial aggregates and the supply of reserve money.